(untitled) - Wright, Reg (Oxford, 1998)
Jennifer Walton is a nurse. She is quiet and careful and sensible, but she has a young brother, Richrd. Richard is not careful or sensible. He is always borrowing money, he never keeps a job for long, he's been in trouble with the police. Jennifer worries about him a lot. And when one day the police come asking questions about him, Jennifer fears the worst
Keywords: English fiction,English literature; 20th century